Analisis Nilai Ekonomi dan Kelayakan Berbasis Skala Usahatani Padi Sawah di Kecamatan Panai Hulu - Tanjung, Ade Firmansyah; Nurhajijah, N; Siregar, Aflahun Fadhly; Salsabila, S (Journal Galung Tropika, 2022)
Up to now, employment in rural areas is still dominated by the primary sector, namely the agricultural sector. Especially the people in Panai Hulu Subdistrict, Labuhan Batu Regency, North Sumatra, still rely on the farming sector as a livelihood as a driver of the economy and to meet the needs of family life, which has a positive impact on improving the welfare of farmers. This study aimed to analyze the economic value and feasibility based on the scale of lowland rice farming in Panai Hulu District. The research analysis method is carried out by calculating the economic value and feasibility of farming by taking into account the economic value (production costs, revenue, income) and the feasibility value (B/C and R/C). The data collection method for this research was through interviews and field observations. The results showed the economic value and feasibility by grouping the average farmer with a land area scale of 0.5–1 ha per planting season. The research resulted in a production of 3,685 kg, total revenue of Rp. 15,430,370, the value of income obtained is Rp. 10,077,410. While the feasibility value of the Benefit–Cost Ratio (B/C) is 1.9 and the Revenue/Cost Ratio (R/C) is 2.9. Farmers with a scale of land area >1 ha per planting season produce 6,812 kg of production, total revenue of Rp. 28,363,030, and the value of the income obtained is Rp. 15,564,404. The Benefit – Cost Ratio (B/C) feasibility value is 1.3, and the Revenue/Cost Ratio (R/C) is 2.3. This value shows that the farming carried out is still quite feasible and appropriate compared to the costs incurred by farmers and has a positive impact on meeting the living needs of the farmer’s family.